(untitled) (Journal of Scientific Research, 2013)
In this present study, the various plant parts of Ficus hispida were subjected to thrombolytic and antimicrobial activities. The thrombolytic activities were assessed by using human blood samples and the results were compared with standard streptokinase (SK). In this study, the methanol soluble fraction (MSF) exhibited highest thrombolytic activity (50.12±1.91). However, significant thrombolytic activity was demonstrated by the crude ethanol extract (CEE) and n-hexane soluble fraction (HSF) of F. hispida (21.74±0.69) and (42.22±1.42) respectively. On the other hand, the n- hexane soluble fraction (HSF) and methanol soluble fraction (MSF) of ethanol extract revealed moderate antibacterial activity against some microorganisms used in the screening. Keywords: Ficus hispida; Thrombolytic activity; Antimicrobial activity. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.11988 J. Sci. Res. 5 (2), 393-397 (2013)